Influence of transport temperature profiles on wine quality. (September 2021) - Jung, Rainer; Kumar, Keshav; Patz, Claus; Rauhut, Doris; Tarasov, Andrii; Schüßler, Christoph
Highlights: Simulation of wine transport conditions in a climate chamber. Temperature-time equivalence calculation for study of wine quality changes. UV–vis + sensory analysis as a tool to monitor temperature-related changes in wine. Higher sensory changes for fruity lighter wines after simulated transportation. Abstract: The temperature effect of simulated transport conditions on wine quality was investigated. Transport situations were simulated in a climate chamber for five wines representing international wine styles: one sparkling, two white and two red still wines. The wines were exposed to temperature scenarios over a maximum time of 42 days at temperature ranges between 15 and 40 °C and the control storage at 15 °C. Analytical and sensory results demonstrated that a significant temperature influence, calculated as a temperature-time equivalence needs to be reached before quality effects are observed. The wines of a fruity and lighter style (red Pinot Noir and Sauvignon Blanc wines from 2017 vintage) were more sensitive than the wines with higher alcohol and wooden aging (red Bordeaux and Chardonnay wines from 2015 vintage). Except for the Champagne, sensory examinations showed a regular linear trend with exposure severity starting at the time equivalence at 15 °C. The sensory results correlated well with the UV–vis and HS-SPME-GC–MS results.